The Use of the Passive Marker bei in Spoken Mandarin. Issue 1 (2nd January 2019) - Cook, Angela
Abstract : The passive marker bei has been the subject of a significant quantity of linguistic research; however the bulk of studies to date have focussed on its use in written Chinese. This article provides a snap shot of current usage of bei in spoken Mandarin based on a corpus of Chinese chat show transcripts and assesses the claims made about the bei construction in the literature. Careful examination of the data reveals that this grammatical marker is both less sensitive to a number of constraints outlined in the mainstream literature and, at the same time, more responsive to a range of different contextual factors, some of which seem to have been overlooked in previous treatments of Mandarin grammar. In particular, it is found that many non-grammatical factors play a role in determining the behaviour of the passive marker bei . The analysis demonstrates that spoken data can reveal interesting insights in to the complexity of the grammatical system, insights that may possibly not be so readily apparent on the basis of written texts and grammaticality judgments alone. This suggests that other morpho-syntactic features of Modern Standard Chinese could likewise benefit from a detailed analysis of their behaviour in spoken interactions.